2001
DOI: 10.1128/jvi.75.22.10843-10855.2001
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Interleukin-2 Administration Corrects the Cell Cycle Perturbation of Lymphocytes from Human Immunodeficiency Virus-Infected Individuals

Abstract: Human immunodeficiency virus (HIV)-induced immunodeficiency is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
34
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 59 publications
(85 reference statements)
9
34
0
Order By: Relevance
“…46,48,49,102,[116][117][118][119][120][121][122] Thus, the addition of antibodies to IL-10 or the addition of IL-12 have a preventive effect on abnormal programmed cell death induction in response to in vitro stimulation in HIV-infected persons. 46,48 Moreover, we found that IL-12, which upregulates TH1 functions and prevents TCR-mediated CD4 T-cell apoptosis, also prevents Fas-mediated apoptosis of CD4 þ T cells from HIV-infected persons.…”
Section: Preventive Effect Of Cytokinesmentioning
confidence: 99%
See 1 more Smart Citation
“…46,48,49,102,[116][117][118][119][120][121][122] Thus, the addition of antibodies to IL-10 or the addition of IL-12 have a preventive effect on abnormal programmed cell death induction in response to in vitro stimulation in HIV-infected persons. 46,48 Moreover, we found that IL-12, which upregulates TH1 functions and prevents TCR-mediated CD4 T-cell apoptosis, also prevents Fas-mediated apoptosis of CD4 þ T cells from HIV-infected persons.…”
Section: Preventive Effect Of Cytokinesmentioning
confidence: 99%
“…Cytokines, in contrast, prevented both the apoptotic phenotype and the cell death by preserving mitochondrial membrane potential staining for the argyrophilic Nucleolar Organizing Regions (AgNOR) and the subcellular localization of nucleolin in confocal microscopy. [122][123][124][125][126][127] Importantly, the HIV-associated cell cycle dysregulation is exacerbated by in vitro treatment with mitogens and appears to be correlated with induction of T-cell apoptosis; 122,123,126 however, these cell cycle perturbations and apoptosis are reduced after exogenous administration of IL-2 in vitro. 122 In mitogen-activated lymphocytes from HIV-infected patients, the inappropriate activation of the cyclin B1/p34 cdc2 kinase complex is temporally associated with increased threonine phosphorylation, augmented fragmentation, and prominent extranuclear and cell surface localization of nucleolin.…”
Section: Cell Cycle Dysregulationmentioning
confidence: 99%
“…131 On the other hand, in vitro treatment with IL-2 corrects the cell-cycle deregulation observed in CD8 þ T cells from HIV-positive patients, indicating a role of cytokine deficiency in apoptosis of CD8 þ T cells. 132 Exogenous cytokines like IL-2, IL-10, IL-12 and IL-15 can inhibit apoptosis of CD8 þ T cells in vitro [133][134][135][136] and augment in vitro the immune functions of peripheral blood mononuclear cells (PBMCs) from HIV-infected patients, 137 further supporting the involvement of cytokines in the CD8 þ T-cell loss in HIV infection. An altered cytokine profile toward a Th2 type (IL-4, IL-5, IL-6, IL-10) has been suggested; 138 however, this has been challenged in other studies where an intracellular staining assay was used to determine cytokine production in HIV-infected patients.…”
Section: Role Of Cytokine Milieu In Hiv-specific Cd8 þ T-cell Apoptosismentioning
confidence: 99%
“…Furthermore, increased levels of apoptosis were found to be associated with deregulated expression of cell-cycle proteins in CD4 þ and CD8 þ T cells from HIV-infected individuals. 85,132 Bcl-2 is a molecule that mediates both apoptosis and cell-cycle regulation, 159,160 something described also for other Bcl-2 family molecules. 161 We hypothesize that a potential deregulation of Bcl-2-like molecules in HIV-specific CD8 þ T cells could be the linker between a cell-cycle deregulation, activation and apoptosis sensitivity.…”
Section: Toward Understanding the Molecular Mechanism Of Hiv-specificmentioning
confidence: 99%
“…Conversely, IL-2-induced cell cycle progression from G 1 to S phase, even without proliferation, is sufficient to prevent anergy (11). In addition, it was shown that CD4 ϩ T cells from HIV-infected patients exhibit deficient IL-2 autocrine function, and the addition of exogenous IL-2 is sufficient to correct cell cycle abnormalities characteristic for these cells (12). In anergic T cells, the downregulation of IL-2 gene expression is achieved by an active process (13).…”
mentioning
confidence: 99%